A pedagogical proposal for teaching object-oriented programming: Implementation through the educational software Wollok - Spigariol, Lucas (2016 IEEE Congreso Argentino de Ciencias de la Informática y Desarrollos de Investigación (CACIDI), 2016)
Since years, the prevalent programming paradigm in professional world of software development is the object-oriented one. However, the inertia of traditional forms of programming coupled with outdated learnings in the field, often leading to object programming languages used with a procedural approach and then waste their potential and fall into few robust software. Assuming the influence of university careers systems in the dynamics of software development industry, it is essential to address the educational processes that occur in their area. This paper presents some pedagogical choices about how to teach programming under the paradigm of OOP and use of an educational software, called Wollok, which was designed by university teachers to accompany and sustain this process. It consists in a development environment that includes a new programming language based on the classic Smalltalk ideas with more modern languages own characteristics. Its simplicity allows focus on the main concepts of paradigm - objects, messages, polymorphism- and gradually incorporate more complexity - classes, inheritance, mixins-according to the progress of the learning process.